Performance of Free-space Optical Communication Systems using Optical Amplifiers under Amplify-forward and Amplify-received Configurations - Darusalam, Ucuk; Raj, Arockia Bazil; Zulkifli, Fitri Yuli; Priambodo, Purnomo Sidi; Rahardjo, Eko Tjipto (Makara Journal of Technology, 2020)
With the growth of digital technology in the stage of industrial revolution 4.0, the demand for broadcasting large amounts of information to last mile users has increased. Free-space optical (FSO) communication is one of the telecommunication platforms that has shown immense potential in meeting the demand for information broadcasting. In this work, the performance of FSO communication based on wavelength division multiplexing with a data rate of 80 Gbps is investigated through simulations. The configuration of optical amplifiers in the FSO system is set up on the basis of the amplify-forward and amplify-received configurations to expand the network. The investigation is aimed at identifying the best optical signal amplification between an erbium-doped fiber amplifier (EDFA) and a semiconductor optical amplifier (SOA) under an atmospheric channel. Simulation results show that the EDFA performs better than the SOA in terms of the optical signal amplification for eight channels of the C band. The maximum optical propagation path length under the atmospheric channel for the amplify-forward and -received schemes using the EDFA is 1.7 km, with the bit error rate achieved at 10−6.